Mengilhami Reformasi Pastoral Charles Borromeo dalam Praktik Pastoral di Era Digital - Raimundus Awur; Oktovianus Son; Krisanto Lafu Babu (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Inspiring means providing encouragement or motivation for someone to think, create, or take action. This word is often used to describe a positive influence that drives creativity, ideas, or motivation in actions. For example, a work of art or noble deed can